Agressão interespecífica em lagostins: invasões biológicas, dominância e exclusão competitiva (Crustacea: Astacidea) - Dalosto, Marcelo Marchet (2016)
Interspecific aggression is a common ecological phenomenon, but is still very poorly understood. It is related to the obtention of resources, geographic distribution patterns and species replacement, in the case of biological invasions. A better understanding of this issue may contribute to different areas, such as ecology, evolution, biogeography and conservation biology. Decapod crustaceans are a good model group to study interspecific aggression: they respond well to laboratory conditions, and aggression is an important aspect of the ecology of many species. The goal of this thesis is to use decapods as models to investigate interspecific aggression in three different contexts: biological invasions, competitor naïveté and experimental designs. In the first chapter, we investigate the interaction of the native crayfish Parastacus brasiliensis with the invasive Procambarus clarkii, to better understand the consequences of a possible interaction of these species in nature, considering that the invasive species has not yet encountered the native. In experiments with size-matched animals, the invader won more interactions, was more aggressive, reached the resource first and kept possession of the resource for longer than the native species. Interspecific fights escalated faster than intraspecific fights. These results mean that P. clarkii is a serious threat to native species, especially considering that this invader reaches larger sizes and is more fecund than native species of similar niches. In the second chapter, we investigated the interspecific aggression between P. clarkii and three other invasive crayfish species: Orconectes limosus, Pacifastacus leniusculus and Astacus leptodactylus. These interactions were compared with P. clarkii intraspecific fights. All fights were repeated along three consecutive days. In intraspecific fights, the duration of the first bout, mean duration of bouts, total fighting time, number of bouts and highest aggressive level differed between days: they were higher in the first day in comparison to the second and third days. In contrast, in interspecific fights only the highest aggressive level differed, between the first and second days of the interactions with O. limosus. We also found differences between the experimental groups in the first day, regarding the latency and time to the highest aggression level, indicating that interactions with P. leniusculus tend to escalate faster than the others. In the species combinations we tested, there seems to be no dominance hyerarchies between species without previous co-existence, since aggressive levels did not decrease over time, suggesting that the inability to form stable dominance might be an important factor in biological invasions. In the third chapter we investigated aggressive interactions between the crayfish P. brasiliensis and a native competitor, the anomuran Aegla longirostri, aiming to test which criteria is the most parcimonious to outline laboratorial experiments between competitors with different morphologies. We observed fights of interspecific pairs with random-sized animals, for which we determined the size difference, weight difference and weapon strength difference. We used a series of models to test if these variables were able to predict the winning species, number of aggressive bouts, duration of the first bout, mean duration of bouts, total fighting time, latency period and time until the highest aggression. The strength difference was able to predict the winning species, with the probability of A. longirostri being the winner increasing as the difference in weapon strength decreased, meaning that this aeglid has an advantage when both animals are matched for strength. This also indicates that, between competitors with different body shapes, weapon strength may be the best predictor of success in aggressive interactions. The size difference was related to the time until the maximum aggression, and fights escalated faster as the size difference between contestants decreased. This could be due to the fact that large animals perceive themselves as potential winners of fights, even though such hypothesis should to be tested in the future. Overall, our results indicate that interspecific aggression is an important phenomenon to all investigated species, but this issue clearly requires an overall framework that unifies the scarce literature around this subject, to provide clear directions for future research on this topic.